Eﬀectiveness of a Mobile Paddy Expert System in Pest Diagnosis - Janarthanan Rengaraju; Senthil kumar Manivasagam (Journal of Extension Education, 2022)
'Crop doctor' is a component in a mobile application developed by Tamil Nadu Agricultural University (TNAU) for diagnosing pest and diseases in paddy and aids in availing management solutions. The study was conducted among paddy growers in Tamil Nadu through an 'after only' experimental design to ﬁnd out the diagnostic usability of 'Crop doctor' in Paddy Expert System mobile application of TNAU in diagnosis of pest and disease in paddy. Diagnostic Usability of crop doctor component among the respondents revealed that overall eﬀectiveness of the mobile application was found to be at 73.20 percent.